Hemimasticatory spasm: a series of 17 cases and a comprehensive review of the literature - Yoshida, Kazuya (Frontiers in Neurology, 2024)
Hemimasticatory spasm (HMS) is a rare movement disorder characterized by paroxysmal spasms or twitches of the unilateral jaw-closing muscles. This study aimed to comprehensively evaluate the clinical features of patients with HMS. Data from 17 patients newly diagnosed with HMS (12 females and 5 males; mean age at onset: 46.7 years) who visited our department were retrospectively analyzed, and a literature search based on electronic medical databases from their inception until November 30, 2023, was conducted. A manual search was conducted for articles cited in the related literature. A total of 117 cases (72 females and 45 males; mean age at onset: 37.1 years) from 57 studies were analyzed. The muscles involved were the masseter (97.4%), temporalis (47.9%), and medial pterygoid (6%). Morphea or scleroderma was observed in 23.9% of the patients, and facial hemiatrophy in 27.4%. In 17.9% of the cases, Parry-Romberg syndrome was either complicated or suspected. Typical electromyographic findings included the absence of a silent period during spasms (23.9%) and irregular brief bursts of multiple motor unit potentials. Oral medicines, such as clonazepam or carbamazepine, alleviated the symptoms for some patients but were often unsatisfactory. Botulinum toxin therapy was effective in most cases. Recently, microvascular decompression surgery is increasingly being used, resulting in complete relief in some cases. In conclusion, highly effective modalities are currently available, and it is necessary to raise awareness of HMS to ensure that it can be diagnosed and treated accurately by both medical and dental professionals.